A review on current aspects and diverse prospects for enhancing biogas production in sustainable means. (February 2015) - Divya, D.; Gopinath, L.R.; Merlin Christy, P.
Abstract: A key strategy allied with today is to develop an alternative energy source instead of fossil fuels in order to compensate present energy need in addition to reduce environmental concerns owed by pollution and global warming. Energy generation in feasible manner without possessing environmental crash is a difficult task where alternative concepts were requisite to ensure sustainable development with accessible technologies. Further advances triggered renewed attention in biogas production technology while it has great impacts on diminishing major economic issues raised in the world. Since the light of these strategies, the present review intended to critically evaluate the recent technological advances and promising prospects coupled with various aspects of biogas production such as sustainable feedstock utilization, microbial and enzyme dynamics, parameter optimization and process segregation, for enhancing this technology in outlook. Appropriate selection, co-digestion, and biotransformation offers a great challenge that crafts substrate to become more energy efficient, besides to trim down the constraints behind principle biomass utilization. A basic framework for process stimulation with microorganisms and enzyme preparations explored that further experimental trials by means of identification of efficient microbes and standardization of enzyme dynamics would augment the feasibility of energy flow during anaerobic digestion. Accordingly, the optimization of various parameters is preferred to accelerate biogas production by resolving the problems occur during anaerobic digestion. Despite the development of multi-stage digester designs intend a breakthrough for process segregation and existing opportunities in this aspect needed further research interest to attain better performance of the system. Moreover, advance simulation approaches using projected prospects from this review would realize significant enhancement of biogas production in the predictable manner.